Baseline significant tricuspid regurgitation is associated with higher mortality in transcatheter aortic valve replacement: systemic review and meta-analysis. Issue 7 (July 2019) - Prasitlumkum, Narut; Kittipibul, Veraprapas; Tokavanich, Nithi; Kewcharoen, Jakrin; Rattanawong, Pattara; Angsubhakorn, Natthapon; Mao, Michael A.; Gillaspie, Erin A.; Cheungpasitporn, Wisit
Abstract : Introduction: Significant tricuspid regurgitation is a well recognized indicator of right ventricular dysfunction. Recent studies have shown that significant tricuspid regurgitation is potentially associated with increased mortality in patients with severe aortic stenosis who underwent transcatheter aortic valve replacement (TAVR). However, data remained sparse and inconclusive. Thus, we performed a systematic review and meta-analysis of the literature to assess the association between significant tricuspid regurgitation and mortality in post TAVR patients. Hypothesis: Significant tricuspid regurgitation is predictive for higher mortality in patients undergoing TAVR. Methods: We comprehensively searched the databases of MEDLINE and EMBASE from inception to October 2018. Included studies were published observational studies that reported multivariate analysis of the effects of significant tricuspid regurgitation on all-cause mortality among patients undergoing TAVR. Data from each study were combined utilizing the random-effects, generic inverse variance method of DerSimonian and Laird to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Nine cohort studies from August 2011 to May 2018 consisting of 27 614 patients with severe aortic stenosis undergoing TAVR (6255 with and 21 359 without significant tricuspid regurgitation) were included in this meta-analysis. The presence of significant tricuspid regurgitation was associated with higher all-cause mortality (pooled OR = 2.26, 95% CI: 1.45–3.52, P  < 0.001). We found that all-cause mortality remained statistically substantial in all subgroups (30-day all-cause mortality: OR = 2.05, 95% CI: 1.20–3.49, P  = 0.009; midterm all-cause mortality: OR = 9.67, 95% CI: 2.44–38.31, P  = 0.001; and long-term all-cause mortality: OR = 1.48, 95% CI: 1.19–1.85, P  < 0.001). Funnel plots and Egger's regression asymmetry test were performed and showed no publication bias. Conclusion: Significant tricuspid regurgitation increased risk of mortality by up to two-fold among patients with severe aortic stenosis undergoing TAVR. Our study suggests that significant tricuspid regurgitation should be considered a component of risk stratification tools. Abstract : Supplemental Digital Content is available in the text